Endothelin-1 Gene Polymorphisms in Patients with Peripheral Artery Disease. - Es, Mehmet Ugur; Senol, Sefa; Yuksel, Ahmet; Kargun, Kursat (Excerpta Medica Inc-Elsevier Science Inc, 2016)
[Abstract Not Available]
12th International Congress of Update in Cardiology and Cardiovascular Surgery -- MAR 10-13, 2016 -- Antalya, TURKEY